Cancer Stem Cell Plasticity – A Deadly Deal - Thankamony, Archana P.; Saxena, Kritika; Murali, Reshma; Jolly, Mohit Kumar; Nair, Radhika (Frontiers in Molecular Biosciences, 2020)
Intratumoral heterogeneity is a major ongoing challenge in the effective therapeutic targeting of cancer. Accumulating evidence suggests that a fraction of cells within a tumor termed Cancer Stem Cells (CSCs) are primarily responsible for this diversity resulting in therapeutic resistance and metastasis. Adding to this complexity, recent studies have shown that there can be different subpopulations of CSCs with varying biochemical and biophysical traits resulting in varied dissemination and drug-resistance potential. Moreover, cancer cells can exhibit a high level of plasticity or the ability to dynamically switch between CSC and non-CSC statesoramong different subsets of CSCs. The molecular mechanisms underlying such plasticity has been under extensive investigation and the trans-differentiation process of Epithelial to Mesenchymal transition (EMT) has been identified as a major contributing factor. Besides genetic and epigenetic factors, CSC plasticity is also shaped by non-cell-autonomous effects such as the tumor microenvironment. In this review, we discuss the recent developments in understanding CSC plasticity in tumor progression at biochemical and biophysical levels,and the latest in silico approaches being taken for characterizing cancer cell plasticity with implications in improving existing therapeutic approaches.